2005
DOI: 10.1007/s10333-005-0023-5
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for soil conservation towards integrated basin management for sustainable development: A new approach based on the assessment of soil loss risk using remote sensing and GIS

Abstract: Soil suspension in the Cidanau River of western Java, Indonesia, has increased recently, perhaps because of rapid environmental change in this watershed region. The objectives of this research are to assess soil loss risk using remote sensing and GIS and to develop effective guidelines for soil conservation in this watershed. To assess soil loss risk, a new soil loss model based on Universal Soil Loss Equation (USLE) was applied, in which C factor (crop management factor) was estimated using the perpendicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 9 publications
(8 reference statements)
0
20
0
1
Order By: Relevance
“…The fact that forest in this area has been steadily increasing indicates that the regional environmental policies in this watershed have begun to show their effects to regulate land use pattern and to mitigate the imprudent land development (Amato et al, 2016). Since the increase of forest in the hillside reduces the surface soil loss rates from the sparsely vegetated lands to the river, soil suspension of the river water could get lower, then, the sedimentation on the river floor in the river streams would decline (Yoshino & Ishioka, 2005). Consequently, the frequency and the severalty of flooding of Brantas River will decrease in the near future.…”
Section: Driving Forces Of Land Use Changementioning
confidence: 99%
“…The fact that forest in this area has been steadily increasing indicates that the regional environmental policies in this watershed have begun to show their effects to regulate land use pattern and to mitigate the imprudent land development (Amato et al, 2016). Since the increase of forest in the hillside reduces the surface soil loss rates from the sparsely vegetated lands to the river, soil suspension of the river water could get lower, then, the sedimentation on the river floor in the river streams would decline (Yoshino & Ishioka, 2005). Consequently, the frequency and the severalty of flooding of Brantas River will decrease in the near future.…”
Section: Driving Forces Of Land Use Changementioning
confidence: 99%
“…The Rawa Danau swamp area downstream faces eutrophication and sedimentation threats [40,41], and the water quality and average flow of the Cidanau river have decreased [41].…”
Section: Cidanau: Funding By a Private Water Company Management Of Imentioning
confidence: 99%
“…Pandey et al (2007) divided the Karso watershed of Hazariabagh, Jharkhand State, India, into 200 9 200 m grid cells and average annual sediment yields were estimated for each cell of the watershed to identity the critically prone areas of watershed. Recent studies (Pandey et al 2007;Yoshino and Ishioka 2005;Sharma et al 2001;Khan et al 2001;Sidhu et al 1998) revealed that remote sensing (RS) and geographic information system (GIS) techniques are of great use in characterization and prioritization of watershed areas using land use/land cover methods (Kulkarni et al 2014;Waikar and Nilawar 2014;Warrier and Manjula 2014). Conventional method to drive morphological parameters is expensive, time consuming and more prone to error.…”
Section: Introductionmentioning
confidence: 99%